Education Game of Javanese Language for 2nd Grade of Elementary Schools - Irse Surya Bagaskara (SISFORMA, 2016)
Local language is the language that is often used to communicate in daily life, but in the case studies in the field are very different. Some kids are more frequently using Indonesian language to communicate with each other. And it makes kids dont understand about Java language lessons at school. Because of that we hope this game "Si Nau" can be the alternate of learning media, so that kids can be more understand about java language lessons at school.In this research contains the result about how to formulate an interesting game about java language. formulate a game that include gameplay, delivery method so that kids can understand about Java language, the impact of game "Si Nau" against children. The survey result of this research, the most of children become interested in Java language lessons at school or in the neighborhood they lives, the children are also able to understand the java language lessons at school. and some parents also makes this game "Si Nau" as the alternate of learning media at home